Pengaruh Cash Holding Dan Financial Leverage Terhadap Income Smoothing (Studi Empiris Perusahaan Sektor Transportasi dan Logistik yang Terdaftar di BEI tahun 2019-2023) - Nice Agustin Ahmad; Wydia Natassa Br Sinulingga; Aminah Aminah; Muhamad Aspuri; Ibram Pinondang Dalimunthe (CV. ITTC INDONESIA, 2025)
This study attempts to explore the influence of two main factors, Cash Holding and Financial Leverage, on Income Smoothing practices in the Transportation and Logistics sector listed on the Indonesia Stock Exchange in the period 2019 to 2023. With a quantitative approach and secondary data, this study selects samples based on purposive sampling from a population consisting of 37 companies, which ultimately resulted in 18 company samples. The Eckel Index is used to measure Income Smoothing, while the relationship between independent and dependent variables is tested using logistic regression through Eviews 12.0 software. The results of the study indicate that Cash Holding and Financial Leverage, as measured by the Debt to Equity Ratio (DER), have a significant influence on Income Smoothing.